2021
DOI: 10.3390/ma14237404
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Corrosion Behaviors of Ti6Al4V Alloy Implant Biomaterial under Metabolic Perturbation Conditions in Physiological Solutions

Abstract: The corrosion of implant biomaterials is a well-known critical issue when they are in contact with biological fluids. Therefore, the reactivity of Ti6Al4V implant biomaterials is monitored during immersion in a Hanks’ physiological solution without and with added metabolic compounds, such as lactic acid, hydrogen peroxide, and a mixture of the two. Electrochemical characterization is done by measuring the open circuit potential and electrochemical impedance spectroscopy performed at different intervals of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…Recent studies suggested that BSA adsorbs on titanium surfaces by electrostatic interactions or chemisorption through amino/ www.nature.com/scientificreports/ carboxylate groups, decreasing the rate of cathodic reduction of H 2 O 2 [46][47][48] . The same behavior has been reported in the addition of the CLH to the H 2 O 2 -containing solutions, which significantly blocks the cathodic site by adsorption on the surface, resulting in lower values of the OCP 28,29 . This does however not mean that the BSA and CLH inhibit the corrosion of Ti in the severe inflammatory medium and it seems necessary to perform PDP and EIS tests for further electrochemical studies.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Recent studies suggested that BSA adsorbs on titanium surfaces by electrostatic interactions or chemisorption through amino/ www.nature.com/scientificreports/ carboxylate groups, decreasing the rate of cathodic reduction of H 2 O 2 [46][47][48] . The same behavior has been reported in the addition of the CLH to the H 2 O 2 -containing solutions, which significantly blocks the cathodic site by adsorption on the surface, resulting in lower values of the OCP 28,29 . This does however not mean that the BSA and CLH inhibit the corrosion of Ti in the severe inflammatory medium and it seems necessary to perform PDP and EIS tests for further electrochemical studies.…”
Section: Resultssupporting
confidence: 76%
“…The passive protective film on titanium in these conditions start to undergo degradation, accelerating corrosion rate and causing surface roughening and formation of intensely hydrated porous TiOOH compound [22][23][24][25] . Recent studies showed that the combination of albumin and H 2 O 2 accelerated the corrosion rate of CP-Ti and Ti-6Al-4V 26,27 and the presence of lactic acid and H 2 O 2 decreased the corrosion resistance considerably 28,29 . As a result of the complicated in vivo environment, corrosion of Ti…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 7 , R s represents the resistance of the solution between the reference electrode and the working electrode, R 1 is the specific resistance of the pure Ni layer, R 2 is the specific resistance of the Ni/nano-TiC composite layer and CPE is a constant phase element, which was used to simulate impedance data when the Nyquist diagram was not a perfect semicircle, possibly due to the uneven and inhomogeneous surface of the electrode. The impedance of such an electrochemical system with a CPE is expressed by Equation (2) [ 30 , 31 ]. where the CPE parameter, α, is also known as the CPE exponent and Q is the magnitude of CPE measured in F cm −2 s α −1 ; j is an imaginary number, j = ; is the angular frequency expressed in rad s −1 ; and f is the frequency in Hz (2π f ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 b and Figure 8 b, which represent the impedance modulus as a function of frequency, show that the slope of the transition region between the limits of the two asymptotes, indicating the power of the dependency of the imaginary part of the impedance on the frequency [ 30 ], was different for the two layers. The analysis of the slopes showed a higher value for the Ni/nano-TiC layer that slightly increased for both immersion periods.…”
Section: Resultsmentioning
confidence: 99%